2015
DOI: 10.1137/13094503x
|View full text |Cite
|
Sign up to set email alerts
|

Iterative Rounding Approximation Algorithms for Degree-Bounded Node-Connectivity Network Design

Abstract: Abstract. We consider the problem of finding a minimum edge cost subgraph of a graph satisfying both given node-connectivity requirements and degree upper bounds on nodes. We present an iterative rounding algorithm of the biset LP relaxation for this problem. For directed graphs and k-out-connectivity requirements from a root, our algorithm computes a solution that is a 2-approximation on the cost, and the degree of each node v in the solution is at most 2b(v) + O(k) where b(v) is the degree upper bound on v. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…approximation for k-Connected Subgraph; the latter result holds for all values of k. In joint work with Nutov [7], the authors of [8] strengthened their analysis and obtained an (O(1), O(1)b(v) + O(k)) approximation for Elem-SNDP. By combining the approach of Cheriyan and Vegh [2] for the k-Connected Subgraph problem without degree bounds with the algorithm of [8] for the degree bounded Rooted k-Connectivity problem and the algorithm of [7] for the degree bounded Elem-SNDP problem, one obtains an (O(1), O(1)b(v) + O(k)) approximation for the degree bounded k-Connected Subgraph problem when the number of nodes is at least (k − 1) 3 − k.…”
Section: Related Workmentioning
confidence: 91%
See 4 more Smart Citations
“…approximation for k-Connected Subgraph; the latter result holds for all values of k. In joint work with Nutov [7], the authors of [8] strengthened their analysis and obtained an (O(1), O(1)b(v) + O(k)) approximation for Elem-SNDP. By combining the approach of Cheriyan and Vegh [2] for the k-Connected Subgraph problem without degree bounds with the algorithm of [8] for the degree bounded Rooted k-Connectivity problem and the algorithm of [7] for the degree bounded Elem-SNDP problem, one obtains an (O(1), O(1)b(v) + O(k)) approximation for the degree bounded k-Connected Subgraph problem when the number of nodes is at least (k − 1) 3 − k.…”
Section: Related Workmentioning
confidence: 91%
“…Recently, Nutov [18] considered several degree bounded network design problems with element and vertex connectivity requirements. Nutov showed that one can combine the augmentation framework of Williamson et al [20] with iterated rounding techniques in order to construct a solution that violates the degree bounds by a multiplicative factor that is exponential in k. Some of Nutov's results include an (O(log k), O(2 k )b(v)) approximation for Elem-SNDP and Rooted k-Connectivity, and an (O(k), O(2 k )b(v)) approximation for k-Connected Subgraph; the latter result holds for all values of k. Shortly after, Fukunaga and Ravi [8] significantly improved the approximation guarantees for these problems; their algorithms are based on iterated rounding and their analyses use a novel technical insight. The results of [8]…”
Section: Related Workmentioning
confidence: 98%
See 3 more Smart Citations